Efektivitas Pembelajaran Tokoh Alkitab dengan Positive Action Bible Curriculum terhadap Karakter Anak Didik - Mulianto Mulianto; Fendhy Ongko; Ferry Setiawan Budi; Ferry Yeferson Tulle; Henry Leonardi Sutanto (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2023)
The rapid development of information and communication technology has significantly impacted children's lives, bringing both positive and negative consequences. While it facilitates access to information and communication, technology also introduces challenges such as a decline in learning enthusiasm, entertainment addiction, and exposure to harmful content that can damage moral values. Additionally, inadequate parenting practices exacerbate this issue, with many parents failing to integrate Biblical values in raising their children. This study aims to evaluate the effectiveness of the Positive Action Bible Curriculum in character development for children aged 6-12 years at School of Victory. The research employs a quantitative approach with a pre-test and post-test experimental design. The innovation presented in this study is the integration of Christian religious education into character development through a Bible-based curriculum. The results show a significant improvement in the children's cognitive, emotional, and moral development, supporting the ultimate goal of raising a generation that fears God and embodies the character of Christ.